2012
DOI: 10.1002/jat.2725
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid arrests cell cycle and induces apoptosis via ROS‐mediated mitochondrial depolarization and lysosomal membrane permeabilization in human pancreatic cancer cells

Abstract: Oleanolic acid (OA), a pentacyclic triterpenoid, exhibits potential anti-tumor activity against many tumor cell lines. This study aims to examine the anti-tumor activity of OA on pancreatic cancer cells and its potential molecular mechanism. The results showed that the proliferation of Panc-28 cells was inhibited by OA in a concentration-dependent manner, with an IC50 (The half maximal inhibitory concentration) value of 46.35 µg ml(-1) , as determined by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazoliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 48 publications
6
61
1
Order By: Relevance
“…These events mediated the proapoptotic activity of OA on cancer cells ( Figure 4C and 4D). Although the enhanced expression of Bax has been demonstrated to be associated with apoptosis in cancer cells treated with OA for 24 hr (Wei et al, 2012), translocation of Bax and Bim and suppression of Bcl-2 anti-apoptotic function that were dependent on phosphorylation events was more likely to account for the quick detection of apoptosis in cancer cells treated with OA.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…These events mediated the proapoptotic activity of OA on cancer cells ( Figure 4C and 4D). Although the enhanced expression of Bax has been demonstrated to be associated with apoptosis in cancer cells treated with OA for 24 hr (Wei et al, 2012), translocation of Bax and Bim and suppression of Bcl-2 anti-apoptotic function that were dependent on phosphorylation events was more likely to account for the quick detection of apoptosis in cancer cells treated with OA.…”
Section: Discussionmentioning
confidence: 95%
“…Considering its pleiotropic function and nontoxicity, researchers have been increasingly focused on OA and making efforts to improve its activity and drugability in recent decades (Liby Since that cancer-related deaths keep rising both in developed and developing countries in recent years, the anti-tumor property of OA receives more and more attention. Apoptosis induction has been well known as one of the major mechanisms underlying OA anti-tumor activity on various types of cancer cells (Juan et al, 2006;Martin et al, 2007;Zhang et al, 2007;Shyu et al, 2010;Yan et al, 2010;Feng et al, 2011b;Lucio et al, 2011;Pratheeshkumar et al, 2011;Zhou et al, 2011;Chakravarti et al, 2012;George et al, 2012;Gu et al, 2012;Struh et al, 2012;Wei et al, 2012;Wang et al, 2013). Mechanistically, OA treatment increases the ratio of proapoptotic protein, Bax, to anti-apoptotic protein, Bcl-2, in the outer mitochondrial membrane, facilitates the formation of Bax oligomer, increases the permeability of mitochondrial membrane, releases cytochrome C from inner membrane into cytosol, triggers the caspase pathway through activating Apaf-1, cleaves multiple cellular target molecules including Poly ADP ribose polymerase (PARP) and DNA, and eventually leads to cell death (Martin et al, 2007;Zhang et al, 2007;Shyu et al, 2010;Yan et al, 2010;Zhou et al, 2011;Chakravarti et al, 2012;Wei et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oleanolic acid (3β-hydroxy-olea-12-en-28-oic acid, OA) is the principal active compound present in various traditional Chinese medicinal herbs (including Hedyotis diffusa and Patrinia scabiosaefolia) that have been used to clinically treat various types of human malignancies (24)(25)(26)(27). Previous studies have reported that OA may suppress tumor growth via inhibition of proliferation and promotion of apoptosis of cancer cells (28)(29)(30). To further elucidate the underlying mechanism of anti-cancer activity, the present study used a colorectal cancer (CRC) mouse xenograft model and human umbilical vein endothelial cells (HUVECs) to evaluate the effect of OA on tumor angiogenesis and the activation of the STAT3 and SHH signaling pathways.…”
mentioning
confidence: 99%